2021
DOI: 10.3390/molecules26051395
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Abiotic Elicitors on Expression and Accumulation of Three Candidate Benzophenanthridine Alkaloids in Cultured Greater Celandine Cells

Abstract: Efforts to develop the necessary biotechnologies in Greater Celandine (Chelidonium majus L.), a leading plant resource for the development of plant-derived medicines, have been hampered by the lack of knowledge about transcriptome and metabolome regulations of its medicinal components. Therefore, this study aimed to examine the effect of abiotic elicitors, methyl jasmonate (MJ) and salicylic acid (SA), at different time courses (12, 24, 48, and 72 h), on expression and metabolome of key benzophenanthridine alk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…So far, there is limited reports are available in the field of abiotic elicitor, but now abiotic elicitation is one of the emerging and effective approaches to enhance the production of bioactive compounds through in vitro culture conditions (Kumari et al 2020 ). The impact of abiotic elicitors in plant systems is diverse on cellular processes such as protein synthesis, growth, and development, gene expression, and lipid and carbohydrate metabolisms (Rao and Ravishankar 2002 ; Hashemi et al 2021 ). Recently, various abiotic elicitors were used to modify the cell metabolism of the plant, and these cellular modifications delineated the enhancement of desired phytomolecule production under in vitro conditions (Rodziewicz et al 2014 ; Xu et al 2015 ) reported that treatment of UV-C along with the combination of Methyl jasmonate (MeJA) and Salicylic acid (SA) had a major impact on the enhancement of stilbene biosynthesis in Vitis vinifera cell suspension cultures.…”
Section: Sms Production By Abiotic and Biotic Elicitorsmentioning
confidence: 99%
“…So far, there is limited reports are available in the field of abiotic elicitor, but now abiotic elicitation is one of the emerging and effective approaches to enhance the production of bioactive compounds through in vitro culture conditions (Kumari et al 2020 ). The impact of abiotic elicitors in plant systems is diverse on cellular processes such as protein synthesis, growth, and development, gene expression, and lipid and carbohydrate metabolisms (Rao and Ravishankar 2002 ; Hashemi et al 2021 ). Recently, various abiotic elicitors were used to modify the cell metabolism of the plant, and these cellular modifications delineated the enhancement of desired phytomolecule production under in vitro conditions (Rodziewicz et al 2014 ; Xu et al 2015 ) reported that treatment of UV-C along with the combination of Methyl jasmonate (MeJA) and Salicylic acid (SA) had a major impact on the enhancement of stilbene biosynthesis in Vitis vinifera cell suspension cultures.…”
Section: Sms Production By Abiotic and Biotic Elicitorsmentioning
confidence: 99%
“…In the current investigation, the long-term exposure to 2.4-D was associated with the culture-age effect. Due to the homogeneity of cell suspension cultures and cells coming into close touch with a liquid medium, foreign chemicals like PGRs may have a greater effect on cells [60]. Continuous production of secondary metabolites is impeded by a loss of cell productivity, irregular production patterns, and large variability across periodical subcultures [61].…”
Section: Resultsmentioning
confidence: 99%